Management of failed knee cartilage surgery-an international Delphi consensus statement - Zoe W. Hinton; Eoghan T. Hurley; Richard M. Danilkowicz; Brian Forsythe; Andreas H. Gomoll; Simon Görtz; Christian Lattermann; David Parker; Tim Spalding; Brian R. Waterman; Annunziato Amendola (Elsevier, 2024)
Introduction: Articular cartilage injuries of the knee are a complex and challenging clinical pathology. Objectives: The purpose of this study was to establish consensus statements via a Delphi process on the management of failed knee cartilage surgery. Methods: A consensus process on knee cartilage injuries utilizing a modified Delphi technique was conducted. Seventy-nine surgeons across 17 countries participated in these consensus statements. Eleven questions were generated on the management of failed knee cartilage surgery, with 3 rounds of questionnaires and final voting occurring. Consensus was defined as achieving 80% to 89% agreement, whereas strong consensus was defined as 90% to 99% agreement, and unanimous consensus was defined as 100% agreement with a proposed statement. Results: Of the 11 total questions and consensus statements on the management of failed knee cartilage surgery developed from 3 rounds of voting, 0 achieved unanimous consensus, 10 achieved strong consensus, and 1 achieved consensus. Conclusions: The statements that achieved strong consensus related to revision cartilage indications, contraindications, lesion size, prior procedures, unipolar/bipolar lesions, and salvage procedures. The statement that did not achieve strong consensus was related to the management of a failed osteochondral autograft/allograft.